Legal Protection for Online Loan Borrowers: Perlindungan Hukum bagi Nasabah Pinjaman Online - Armita Latif; Tiara Tiara; Hafiah Hafiah; Andi Muhamad Gufran Anwar (Indonesian Journal of Law and Islamic Law (IJLIL), 2023)
Online loan application services have generated numerous complaints regarding the unauthorized and non-consensual dissemination of personal data by online loan providers without notice and without the owner's permission. Consequently, it is important to study the legal protection of borrowers' personal data in online loan applications, as well as the sanctions for personal data breaches. This article aims to examine the legal protection of borrowers' personal data in online loan applications using a normative legal method through legislative and factual approaches. The study results indicate that legal protection and sanctions for personal data breaches have been regulated in Law No. 11 of 2008 and its amendments concerning Electronic Information and Transactions. However, specific provisions regarding legal protection and sanctions for personal data breaches in online loan services are stipulated in Financial Services Authority Regulation No. 77/POJK.01/2016 concerning Information Technology-Based Peer-to-Peer Lending Services, as emphasized in Article 26 which states that the provider is responsible for maintaining the confidentiality, integrity, and availability of users' personal data and should utilize it with the consent of the personal data owner, unless otherwise specified by legislation. Sanctions for personal data breaches are regulated in Article 47 paragraph (1), which include written warnings, monetary obligations, fines, business activity restrictions, and permit revocation.